Regulatory framework and legal issues in business (part 1) - Domingo, Andrix D. (Benguet : Coaching for Publishing, 2024)
This book is published in the hope that this humble work will be of the great help to readers.
Chapter 1. Nature and form of contract -- Chapter 2. Capacity to buy or sell -- Chapter 3. Effects of the contract when the thing sold has been lost -- Warranties under the consumer act of the Philippines -- Philippine Lemon Law -- Chapter 5. Obligations of the vendee -- Chapter 6. Actions for breach of contract of sale of goods -- Chapter 7. Extinguishment of sale -- Chapter 8. Assignment of credits and other incorporeal rights -- Chapter 9. General Provisions -- Realty Instalment Buyer Protection Act (Maceda Law) -- Subdivision and condominium buyer's protective decree presidential decree no. 957 (P.D. 957) -- The Condominium Act -- Pledfe, Mortage and Antichresis -- Intellectual Property Property Code of The Philippines -- The Philippine Deposit Insurance Corporation.
Keywords: BUSINESS LAW -- PHILIPPINES -- EXAMINATIONS, QUESTIONS ETC